Microangiopathic Hemolytic Anemia and Fulminant Renal Failure: A Rare Manifestation of Pheochromocytoma. (17th December 2019) - Sharma, Nishant; Ravi, Divya; Khan, Mehvish; Sravanthi, Metlapalli Venkata; Aloysius, Mark M.
Abstract : Pheochromocytoma is a rare adrenal tumor that is classically associated with the triad of paroxysmal tachycardia, diaphoresis, and headaches. However, it can have myriad manifestations. We present a case of a 31-year-old male who presented with abdominal pain, hypertensive emergency, and renal failure. Abdominal imaging demonstrated a left adrenal mass. Plasma metanephrines (153 pg/ml, n < 57 ) and normetanephrines (1197 pg/ml, n < 148 ) were noted to be elevated, leading to the diagnosis of pheochromocytoma. Intravenous antihypertensives were utilized to control his blood pressure. Hemodialysis was initiated given the degree of renal dysfunction. The patient subsequently developed hemolytic anemia, requiring the transfusion of multiple units of packed red cells. He developed acute respiratory failure leading to intubation, but was thereafter liberated from the ventilator following clinical stabilization. Uncontrolled hypertension precipitated by pheochromocytoma can cause microangiopathic hemolytic anemia and renal insufficiency. This case is notable not only for the occurrence of this rare presentation, but also for the severity of manifestations in a young male with no known significant comorbidities.